Donor insulin use predicts beta‐cell function after islet transplantation. Issue 10 (14th June 2020) - Shapey, Iestyn M.; Summers, Angela; Yiannoullou, Petros; Khambalia, Hussein; Fullwood, Catherine; Hanley, Neil A.; Casey, John; Forbes, Shareen; Rosenthal, Miranda; Johnson, Paul RV; Choudhary, Pratik; Bushnell, James; et al.
Abstract: Insulin is routinely used to manage hyperglycaemia in organ donors and during the peri‐transplant period in islet transplant recipients. However, it is unknown whether donor insulin use (DIU) predicts beta‐cell dysfunction after islet transplantation. We reviewed data from the UK Transplant Registry and the UK Islet Transplant Consortium; all first‐time transplants during 2008‐2016 were included. Linear regression models determined associations between DIU, median and coefficient of variation (CV) peri‐transplant glucose levels and 3‐month islet graft function. In 91 islet cell transplant recipients, DIU was associated with lower islet function assessed by BETA‐2 scores (β [SE] ‐3.5 [1.5], P = .02), higher 3‐month post‐transplant HbA1c levels (5.4 [2.6] mmol/mol, P = .04) and lower fasting C‐peptide levels (−107.9 [46.1] pmol/l, P = .02). Glucose at 10 512 time points was recorded during the first 5 days peri‐transplant: the median (IQR) daily glucose level was 7.9 (7.0‐8.9) mmol/L and glucose CV was 28% (21%‐35%). Neither median glucose levels nor glucose CV predicted outcomes post‐transplantation. Data on DIU predicts beta‐cell dysfunction 3 months after islet transplantation and could help improve donor selection and transplant outcomes.